2016
DOI: 10.1589/jpts.28.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mirror therapy combined with motor tasks on upper extremity function and activities daily living of stroke patients

Abstract: [Purpose] The objective of this study was to investigate the effects of mirror therapy combined with exercise tasks on the function of the upper limbs and activities of daily living. [Subjects and Methods] Twenty-five stroke patients who were receiving physical therapy at K Hospital in Gyeonggi-do, South Korea, were classified into a mirror therapy group (n=12) and a conventional therapy group (n=13). The therapies were applied for 30 minutes per day, five times per week, for a total of four weeks. Upper limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 21 publications
(23 reference statements)
1
39
1
3
Order By: Relevance
“…The starting point was the hypothesis that the movements of a limb visualized in front of a mirror trigger neuronal connections in the motor cortex concerned (Gurbuz et al, 2016). Neurophysiological and imaging studies using functional MRI were conducted in healthy human subjects, which demonstrated that the excitability of the primary motor cortex increases when the image of one's own moving hand in the mirror is watched (Kim et al, 2016), which supports the idea of neuroplasticity modulation by applying this therapy. Mirror therapy involves overlapping the reflection of the movement of the healthy limb with the affected limb, creating in this way an optical illusion.…”
Section: Mirror Therapy Hypotheses Indications Clinical Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The starting point was the hypothesis that the movements of a limb visualized in front of a mirror trigger neuronal connections in the motor cortex concerned (Gurbuz et al, 2016). Neurophysiological and imaging studies using functional MRI were conducted in healthy human subjects, which demonstrated that the excitability of the primary motor cortex increases when the image of one's own moving hand in the mirror is watched (Kim et al, 2016), which supports the idea of neuroplasticity modulation by applying this therapy. Mirror therapy involves overlapping the reflection of the movement of the healthy limb with the affected limb, creating in this way an optical illusion.…”
Section: Mirror Therapy Hypotheses Indications Clinical Resultsmentioning
confidence: 75%
“…Neuroscientist Ramachandran and coworkers introduced the mirror therapy method to treat phantom limb pain in patients with amputations in 1996 (Guo et al, 2016). They were also the first who suggested that this technique might improve the motor function of a paretic limb after stroke (Kim et al, 2016).…”
Section: Mirror Therapy Hypotheses Indications Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is also proving beneficial for patients suffering unilateral neglect after stroke, in helping relieve phantom limb pain suffered by victims of earthquake as well as to soothe arthritis pain 1,6 . With increase in awareness about the therapy coupled with the boom of online availability of consumer goods, mirror boxes are now also up for sale on the internet and are therefore, more easily available than ever before 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In each case, amputation was necessary after extensive efforts to save the leg. Before amputation surgery, the patients performed several sessions of mirror therapy 1,4,6 .…”
Section: Methodsmentioning
confidence: 99%